<span>Receive a reminder of the bank card for the people of the spring of Tabari?
</span>
Answer:
5 13/15 miles
Step-by-step explanation:
Answer:
Step-by-step explanation:
me too..
For the function
We can use the formula for the axis of symetry, which is
With the values substituted, we get...
Therefore the axis of symmetry is
Let's solve your equation step-by-step.<span><span><span>3<span>(<span><span>2x</span>−1</span>)</span></span>+<span>5<span>(<span>x−3</span>)</span></span></span>=<span><span>4x</span>+7</span></span>Step 1: Simplify both sides of the equation.<span><span><span>3<span>(<span><span>2x</span>−1</span>)</span></span>+<span>5<span>(<span>x−3</span>)</span></span></span>=<span><span>4x</span>+7</span></span>Simplify:<span><span><span>11x</span>−18</span>=<span><span>4x</span>+7</span></span>Step 2: Subtract 4x from both sides.<span><span><span><span>11x</span>−18</span>−<span>4x</span></span>=<span><span><span>4x</span>+7</span>−<span>4x</span></span></span><span><span><span>7x</span>−18</span>=7</span>Step 3: Add 18 to both sides.<span><span><span><span>7x</span>−18</span>+18</span>=<span>7+18</span></span><span><span>7x</span>=25</span>Step 4: Divide both sides by 7.<span><span><span>7x</span>7</span>=<span>257</span></span><span>x=<span>257</span></span>Answer:<span>x=<span><span>257
</span>
</span></span>Let's solve your equation step-by-step.<span><span><span>5−x</span>−<span>(<span><span>2x</span>+3</span>)</span></span>=<span>3+<span>8x</span></span></span>Step 1: Simplify both sides of the equation.<span><span><span>5−x</span>−<span>(<span><span>2x</span>+3</span>)</span></span>=<span>3+<span>8x</span></span></span>Simplify:<span><span><span>−<span>3x</span></span>+2</span>=<span><span>8x</span>+3</span></span>Step 2: Subtract 8x from both sides.<span><span><span><span>−<span>3x</span></span>+2</span>−<span>8x</span></span>=<span><span><span>8x</span>+3</span>−<span>8x</span></span></span><span><span><span>−<span>11x</span></span>+2</span>=3</span>Step 3: Subtract 2 from both sides.<span><span><span><span>−<span>11x</span></span>+2</span>−2</span>=<span>3−2</span></span><span><span>−<span>11x</span></span>=1</span>Step 4: Divide both sides by -11.<span><span><span>−<span>11x</span></span><span>−11</span></span>=<span>1<span>−11</span></span></span><span>x=<span><span>−1</span>11</span></span>Answer:<span>x=<span><span>−1</span>11</span></span>
<span>Espero que esto ayude</span>